Meta-Analisis Landasan Ilmu Pendidikan pada Pengembangan E-book dan Edupark Pembelajaran Fisika - Sari, Ayu Permata; Hamdi, Hamdi (Jurnal Penelitian Pembelajaran Fisika, 2019)
Good education must have educational foundations because it is a fulcrum and benchmarks in education. This study aims to analyze the foundation of educational science towards the development of e-books and eduparchs of learning physics. This research method is a meta-analysis with a sample of 20 articles. The meta-analysis research shows the completeness of the foundation of educational science in the development of e-books and edupark of physical learning by 61.43% with complete categories.